2022
DOI: 10.1007/jhep03(2022)014
|View full text |Cite
|
Sign up to set email alerts
|

Unruh-DeWitt detector in dimensionally-reduced static spherically symmetric spacetimes

Abstract: We study the dynamics of an Unruh-DeWitt detector interacting with a massless scalar field in an arbitrary static spherically symmetric spacetimes whose metric is characterised by a single metric function f(r). In order to obtain clean physical insights, we employ the derivative coupling variant of the Unruh-DeWitt model in (1+1) dimensions where powerful conformal techniques enable closed-form expressions for the vacuum two-point functions. Due to the generality of the formalism, we will be able to study a ve… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 72 publications
0
4
0
Order By: Relevance
“…In entanglement harvesting, one usually considers two such Unruh-DeWitt detectors that are initially uncorrelated and then investigates the condition for these two detectors to get entangled over time. This detector entanglement depends on various scenarios, like due to the motion of the detectors [1,2,8,[21][22][23][24][25], background spacetime geometry [3,7,15,[26][27][28][29][30][31][32][33][34][35][36][37], presence of a thermal bath [38][39][40] to name a few among a plethora of other possibilities [41][42][43][44][45][46]. The experimental prospects of entanglement harvesting have been proposed in atomic physics [47], with superconducting qubits [48], between forward and past light cones [49].…”
Section: Jhep09(2023)180mentioning
confidence: 99%
See 1 more Smart Citation
“…In entanglement harvesting, one usually considers two such Unruh-DeWitt detectors that are initially uncorrelated and then investigates the condition for these two detectors to get entangled over time. This detector entanglement depends on various scenarios, like due to the motion of the detectors [1,2,8,[21][22][23][24][25], background spacetime geometry [3,7,15,[26][27][28][29][30][31][32][33][34][35][36][37], presence of a thermal bath [38][39][40] to name a few among a plethora of other possibilities [41][42][43][44][45][46]. The experimental prospects of entanglement harvesting have been proposed in atomic physics [47], with superconducting qubits [48], between forward and past light cones [49].…”
Section: Jhep09(2023)180mentioning
confidence: 99%
“…The arena of relativistic quantum information (RQI) [1][2][3][4][5][6][7][8][9][10][11][12][13][14][15], which encompasses the field of relativity and quantum information, is getting increasingly more attention due to its ability to probe the quantum nature of physical systems. An important area of research within RQI involves the study of entanglement harvesting from the background quantum field coupled to suitable detectors [1,8,16,17], one of the most prominent of them being the…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one should note that working with linear couplings with detectors switched on for a finite time; one cannot avoid the contributions of the IR cutoff. It compels one to consider the derivative coupling model provided in [77], which gives the Wightman function corresponding to typical Hadamard asymptotics. However, in a few cases, it has been observed that the contributions from the IR cutoff may vanish for infinite switching.…”
Section: Jhep09(2022)106mentioning
confidence: 99%
“…This is known as the Unruh-Davies effect and has a close connection to the Hawking effect [6,7]. The discussion of quantum fields in non-inertial frames and related subjects have been a topic under vigorous investigation throughout the years [8][9][10][11][12][13][14][15][16][17][18][19][20][21][22][23][24][25][26].…”
Section: Introductionmentioning
confidence: 99%